Implementing the CASEL Framework in Lower Elementary Grades: Teachers' Roles, Strategies, and Challenges in Developing Students' Social-Emotional Competencies - Hana Zakiyyah; Yeri Sutopo (Journal of Innovation and Research in Primary Education, 2026)
Social-emotional development in elementary education is critical for holistic student growth, yet implementation remains challenging. This study examined teachers' roles in developing lower-grade students' social-emotional skills through the Collaborative for the Advancement of Social and Emotional Learning (CASEL) approach. A qualitative descriptive case study was conducted at SDN Kauman 2 Elementary School, Juwana District, Indonesia. Data were collected through classroom observations, semi-structured interviews with teachers and principals, and document analysis. Participants were purposively selected lower-grade teachers with direct experience implementing social-emotional learning. Data analysis followed Miles and Huberman's interactive model with triangulation for validation. Teachers effectively implemented all five CASEL competencies—self-awareness, self-management, social awareness, relationship skills, and responsible decision-making—through contextualized strategies integrated across subjects and daily routines. Teachers employed storytelling, role-playing, cooperative learning, and reflective practices while serving as social-emotional role models. Implementation barriers included time constraints, diverse student family backgrounds, and insufficient specialized training. Teachers addressed these through strategic curriculum integration, family engagement, and collaborative school cultures. Findings demonstrate that CASEL can be successfully adapted to culturally distinct contexts when teachers receive adequate support. The seamless integration approach addresses time constraints while enhancing both social-emotional and academic outcomes. Results underscore the necessity of systemic support structures, professional development, and school-wide coordination for sustainable implementation.